Analysis of disordered occupation in upper Macaíba in Jaboatão dos Guararapes/PE (Research, Society and Development, 2021)
Urban centers evolve from a series of factors that are related to promoting growth. Economic and socio-environmental factors must have a harmonious and proportional association in order for an orderly urban growth, which promotes planned and structured spaces, capable of providing its residents with adequate infrastructure. In general, growth takes place amidst the mismatch of these factors, generating disorderly occupations. Issues such as urban drainage, paving and basic sanitation often work in a precarious way, when not, the population lives without these urban structures. The aim of this article is to show an analysis of land occupation in the Morro da Macaíba, located in the neighborhood of Cavaleiro, in the municipality of Jaboatão dos Guararapes/PE. The study sought to verify the process of occupation of the site, through a comparative analysis of quantitative and qualitative data, which occurred at two different times: before the implementation of the Centro-2 line of the Recife subway and after its implementation. It was verified the impacts of urban sprawl, exposed soil and green area suppression, using vectorized images from orthophotocharts of the studied periods to generate quantitative data. It was shown that urban occupation had an increase of 55.22%, while exposed areas and vegetation cover had a reduction of 17.54% and 37.39%, respectively.